Evidence of Morphological and Morphometric Differences in the Sella Turcica of Pteronotus mesoamericanus and P. mexicanus - M. A. Peralta-Pérez; M. Briones-Salas (Animals)
Morphological modifications are a potential mechanism for functional species and phylogenetic diversification. The sella turcica in mammals is a structure associated with the basisphenoid bone and serves as the receptacle for the pituitary gland; however, little is known about the morphological variation that may affect functionality in chiropterans. In this study, we provide morphological and morphometric evidence of differences between populations of Pteronotus mesoamericanus [the Gulf of Mexico] and P. mexicanus [the Pacific Coast] by describing variations in the dimensions of the dorsum sellae and the processus clinoideus caudalis of the sella turcica. We obtained 20 a priori designed measurements of the dorsum of the sella turcica from 243 skulls of both species from various locations in Mexico. The dorsum sellae were found at an average distance of 3.4 mm from the lower edge of the foramen magnum. The dorsum of the sella turcica has a truncated pyramidal shape, with the processus clinoideus caudalis located at the tip of the pyramid. Ten of the measurements obtained were found to be significant for both regions (the Pacific Coast and the Gulf of Mexico). We propose that these measurements be tested in future studies of populations from the Mormoopidae family in the Antilles, Central America, and South America for comparative purposes, and to help distinguish different lineages and functions.